2015
DOI: 10.1016/j.biombioe.2015.04.030
|View full text |Cite
|
Sign up to set email alerts
|

Biochar-mediated reductions in greenhouse gas emissions from soil amended with anaerobic digestates

Abstract: Available online xxxKeywords: Nitrous oxide Anaerobic digestate Biochar Nitrification Denitrification a b s t r a c t This investigation examines nitrous oxide (N 2 O) fluxes from soil with simultaneous amendments of anaerobic digestates and biochar. The main source of anthropogenic emissions of N 2 O is agriculture and in particular, manure and slurry application to fields. Anaerobic digestates are increasingly used as a fertiliser and interest is growing in their potential as sources of N 2 O via nitrificati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(26 citation statements)
references
References 54 publications
1
25
0
Order By: Relevance
“…Ventura et al (2013) also reported significantly reduced cumulative NO 3 − leaching by 75% in an apple orchard, quantified using ion exchange resins over 1 yr. Rizhiya et al (2015) reported higher NO 3 − concentrations in the BC‐amended topsoil, accompanied by reduced N 2 O emissions. A number of laboratory studies have also frequently reported reduced NO 3 − leaching (Lehmann et al, 2003; Laird et al, 2010; Yao et al, 2012; Zheng et al, 2013; Jassal et al, 2015), sometimes accompanied by reports of reduced amounts of extractable NH 4 + and particularly NO 3 − (Sika and Hardie, 2014) and sometimes accompanied by reports of increased amounts of extractable NO 3 − (Van Zwieten et al, 2010; Cayuela et al, 2013; Martin et al, 2015). However, some field studies show no reduction in NO 3 − leaching (Castaldi et al, 2011; Eykelbosh et al, 2015) or even greater NO 3 − leaching than NH 4 + due to BC addition (Güereña et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Ventura et al (2013) also reported significantly reduced cumulative NO 3 − leaching by 75% in an apple orchard, quantified using ion exchange resins over 1 yr. Rizhiya et al (2015) reported higher NO 3 − concentrations in the BC‐amended topsoil, accompanied by reduced N 2 O emissions. A number of laboratory studies have also frequently reported reduced NO 3 − leaching (Lehmann et al, 2003; Laird et al, 2010; Yao et al, 2012; Zheng et al, 2013; Jassal et al, 2015), sometimes accompanied by reports of reduced amounts of extractable NH 4 + and particularly NO 3 − (Sika and Hardie, 2014) and sometimes accompanied by reports of increased amounts of extractable NO 3 − (Van Zwieten et al, 2010; Cayuela et al, 2013; Martin et al, 2015). However, some field studies show no reduction in NO 3 − leaching (Castaldi et al, 2011; Eykelbosh et al, 2015) or even greater NO 3 − leaching than NH 4 + due to BC addition (Güereña et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…This table shows the amount of CO 2 produced by the production of 1 kg of biochar. According to the research conclusion of Zhang [35], the production of 1 kWh electricity can emit 860 g of CO 2 , and from the conclusion of Toyama's research [36], the production of 1 L N 2 can emit 0.12 g of CO 2 .…”
Section: Comparative Analysis Of Basic Physical and Chemical Propertimentioning
confidence: 99%
“…Similar CO 2 emission trends were reported for other biochars. 98,99 The cumulative CO 2 emissions were highest in the soil amended with 0.5 (wt%) followed by 1.0 (wt%) and 3.0 (wt%) CSBC, respectively [ Fig. 8(A)].…”
Section: Soil Respiration: Effect Of Biochar and Biomass Addition On mentioning
confidence: 99%